Influence of the Use of a Mixed Solution of Equal Amounts of Amyl Acetate, Acetone, and Ethanol on the Cleaning of Endodontic Sealer Residues on the Bond Strength of the Fiber Post Cementation System: A Laboratory Investigation - Barros, Antonia Patricia Oliveira [UNESP]; Freitas, Ana Paula Aparecida Raimundo Alves [UNESP]; Kokol, Frederico Guilherme Otto [UNESP]; Souza, Elizangela Maria Pereira de [UNESP]; Junior, Adirson Jorge [UNESP]; Alencar, Cristiane de Melo; Andrade, Marcelo Ferrarezi de [UNESP]; Kuga, Milton Carlos [UNESP] (Bentham Science Publishers, 2024)
Purpose: The study aimed to evaluate the effect of different chemical solutions (ET, 95% ethanol, and ES, experimental solution of amyl acetate, acetone, and 95% ethanol) on the removal of epoxy-based sealer residues (AH, AH Plus Jet, or AD, Adseal) from the adhesive interface between root dentin and universal adhesive in post space third, after 6 months control. Methods: Eighty bovine roots were prepared and randomly divided according to the sealer and cleaning solution: AH Plus Jet + 95% ethanol (AH+ET), Adseal + 95% ethanol (AD+ET), AH Plus Jet + experimental solution (AH+ES), Adseal + experimental solution (AD+ES). Scanning electron microscopy was used to assess the incidence of residue in the post space, and the data obtained were subjected to Kruskal-Wallis/Dunn tests (α=0.05). Bond strength was evaluated in push-out tests, and the data were subjected to ANOVA/Tukey analysis. The adhesive failure pattern was assessed using stereomicroscopy, and the data have been evaluated through incidence frequency. Results: AH+ES and AD+ES showed lower residues incidence and higher bond strength values (p<0.05). Type 4 and 3 failures were observed in the cervical and middle thirds in the groups AH+ET, AD+ET, and AH+ES, AD+ES, respectively. Conclusion: The experimental solution positively influenced the bond strength of the post space.
Keywords: Adhesive; Bond strength; Dentine; Endodontic; Post space; Residue